1984
DOI: 10.1113/expphysiol.1984.sp002778
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Amp as a Possible Mediator of Dopamine Stimulation of Cockroach Gland Cells

Abstract: Isolated salivary glands of the cockroach Nauphoeta cinerea Olivier secrete fluid in response to nerve stimulation or application of dopamine, the acinar cells undergoing a hyperpolarization during secretion. The aim of the present work was to examine whether cyclic AMP acts as a second messenger in the acinar cells to cause the secretory and electrical responses to the transmitter dopamine. Cyclic AMP (10-500 microM) in the bathing solution of isolated glands caused a dose-dependent secretory response but no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…We verified this conclusion by performing a further experiment with two additional AC antagonists, SQ 22536 (Heinrich et al 2001) and MDL 12330A (Gray et al 1984), already assayed in other insect preparations. We injected bees with saline (n ¼ 45) or with SQ 22536 (n ¼ 58) or with MDL 12330A (n ¼ 57) 20 min before acquisition.…”
Section: Experiments 6: Inhibition Of Ac Impairs L-ltm Retentionsupporting
confidence: 56%
“…We verified this conclusion by performing a further experiment with two additional AC antagonists, SQ 22536 (Heinrich et al 2001) and MDL 12330A (Gray et al 1984), already assayed in other insect preparations. We injected bees with saline (n ¼ 45) or with SQ 22536 (n ¼ 58) or with MDL 12330A (n ¼ 57) 20 min before acquisition.…”
Section: Experiments 6: Inhibition Of Ac Impairs L-ltm Retentionsupporting
confidence: 56%
“…From these data, Evans and Green concluded that only one class of receptor with pharmacological properties similar to those of mammalian D1 receptors mediate the effects of DA in Nauphoeta salivary glands. This is in good agreement with the findings that DA increases [cAMP] i in the salivary glands of Nauphoeta (Grewe and Kebabian, 1982) and that cAMP in the bathing solution causes a dose-dependent secretory response (Gray et al, 1984). Interestingly, cAMP fails to hyperpolarize the acinar cell membrane potential as DA does (Gray et al, 1984).…”
Section: +supporting
confidence: 87%
“…This is in good agreement with the findings that DA increases [cAMP] i in the salivary glands of Nauphoeta (Grewe and Kebabian, 1982) and that cAMP in the bathing solution causes a dose-dependent secretory response (Gray et al, 1984). Interestingly, cAMP fails to hyperpolarize the acinar cell membrane potential as DA does (Gray et al, 1984). An explanation could be that the D1-like receptors in the Nauphoeta salivary gland are coupled to phospholipase C (PLC) in addition to adenylyl cyclase .…”
Section: +supporting
confidence: 81%
“…The investigation of the pharmacological properties of the dopamine receptor(s) in these glands could not clearly define which dopamine receptor subtypes are present (51). Furthermore, there are diverse reports on the effect of possible second messengers on saliva secretion in the cockroach N. cinerea, suggesting the involvement of cAMP and/or [Ca 2ϩ ] i (22,23). In the present study, a bumetanide-sensitive [Na ϩ ] i rise could be induced by ionomycin in cockroach salivary acinar peripheral cells.…”
Section: Discussionmentioning
confidence: 97%